2018
DOI: 10.3389/fphys.2018.01127
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Prognosis and Risk Stratification of Brugada Syndrome: A Pooled Analysis of 4,140 Patients From 24 Clinical Trials

Abstract: Background: Male gender has been consistently shown to be a risk factor for a greater number of arrhythmic events in patients with Brugada Syndrome (BrS). However, there have been no large-scale comprehensive pooled analyses to statistically and systematically verify this association. Therefore, we conducted a pooled analysis on gender differences in prognosis and risk stratification of BrS with a largest sample capacity at present.Methods: We searched PubMed, Embase, Medline, Cochrane Library databases, Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…The search strategies contained a combination of two search terms by using the Boolean operator “and” (ie, Brugada syndrome and SCN5A ). In addition, we further searched the reference lists of previous meta‐analyses to identify additional studies. The full electronic search strategy is shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategies contained a combination of two search terms by using the Boolean operator “and” (ie, Brugada syndrome and SCN5A ). In addition, we further searched the reference lists of previous meta‐analyses to identify additional studies. The full electronic search strategy is shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we further searched the reference lists of previous metaanalyses 6,[19][20][21] to identify additional studies. The full electronic search strategy is shown in Table S1.…”
Section: Literature Search and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In Southeast Asia, BrS seems to affect almost exclusively male adults [7]. Pooled analyses indicated that a spontaneous type 1 ECG is an independent risk factor for SCD in males, but not in females, and that male patients are at higher risk of arrhythmic events [8,9]. However, BrS is found throughout the world and in both genders, to whom studies have shown it is transmitted equally [5] as an autosomal dominant disease with incomplete penetrance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Brugada syndrome is about 7-10 times more prevalent in men, and male gender is associated with a higher incidence of ventricular arrhythmias and SCD at diagnosis and follow-up. 17,37,38 However, despite the less favourable prognosis generally observed in men, gender alone may not be an independent prognostic indicator and the majority of men remain asymptomatic. 17,19 Risk stratification in women with Brugada syndrome has been more challenging as most studies have mainly consisted of male participants.…”
Section: Gender-specific Riskmentioning
confidence: 99%